Shamsiah Fakeh : a nationalist or a communist? / Ramlah Adam - Adam, Ramlah (Universiti Teknologi MARA, Shah Alam, 2010)
Shamsiah Fakeh was a well-known personality in the radical and leftist movement before Malaysia’s independence in 1957. She was formerly the leader of AWAS (Angkatan Wanita Sedar), a women’s wing of the Malay Nationalist Party (MNP), or better known as Parti Kebangsaan Melayu Malaya (PKMM). As a leader of the radical group, Shamsiah supported the cooperation of MNP and the Malayan Communist Party (MCP) in their struggles to overthrow the British imperialism in the Federation of Malaya or Persekutuan Tanah Melayu. After the Federation independence in 1957, they continued to struggle wit the reason that the British controlled the affairs of the country. The formation of Malaysia in 1963 gave them another reason to go against the government, where they agreed with the President Sukarno and the Communist Party of Indonesia that Malaysia was a form of neo-colonialism. They worked together with the opposition parties in Malaysia to attack the formulation of Malaysia. They failed in their efforts and struggle but with time and in order to clear their names as communists, they tried to rewrite the history of Malaysia. In their memoirs and books, some of the communist leaders such as Shamsiah Fakeh, Rashid Maidin, Chin, Abdullah C.D. and Suraini Abdullah painted and explained the history differently. They started to call themselves the freedom fighters of the Malaysian Independence and in that view, they consider themselves as nationalists. Question is, are they really nationalists in the right sense of the word? Or did they twist history in order to be the unsung heroes of Malaysia? This paper intends to show the facts of history including their past involvements in the communist struggle to take over this country between 1945-1989 before the Peace Agreement between the Malaysian government and the Malayan Communist Party in Hatyai, Thailand. The people, especially the younger generation may be indifferent or ignorant of the past, but the facts of history are always there to be research and to be told. Shamsiah Fakeh will be the focus of that argument.